Single-cell RNA sequencing of motoneurons identifies regulators of synaptic wiring in Drosophila embryos$nJessica Velten, Xuefan Gao, Patrick van Nierop y Sanchez, Katrin Domsch, Rashi Agarwal, Lena Bognar, Malte Paulsen, Lars Velten & Ingrid Lohmann - Velten, Jessica; Gao, Xuefan; Nierop y Sanchez, Patrick van; Domsch, Katrin; Agarwal, Rashi; Bognar, Lena; Paulsen, Malte; Velten, Lars; Lohmann, Ingrid (Molecular systems biology, 2022)
The correct wiring of neuronal circuits is one of the most complex processes in development, since axons form highly specific connections out of a vast number of possibilities. Circuit structure is genetically determined in vertebrates and invertebrates, but the mechanisms guiding each axon to precisely innervate a unique pre-specified target cell are poorly understood. We investigated Drosophila embryonic motoneurons using single-cell genomics, imaging, and genetics. We show that a cell-specific combination of homeodomain transcription factors and downstream immunoglobulin domain proteins is expressed in individual cells and plays an important role in determining cell-specific connections between differentiated motoneurons and target muscles. We provide genetic evidence for a functional role of five homeodomain transcription factors and four immunoglobulins in the neuromuscular wiring. Knockdown and ectopic expression of these homeodomain transcription factors induces cell-specific synaptic wiring defects that are partly phenocopied by genetic modulations of their immunoglobulin targets. Taken together, our data suggest that homeodomain transcription factor and immunoglobulin molecule expression could be directly linked and function as a crucial determinant of neuronal circuit structure.